Reflexiones teóricas en torno a los negocios internacionales (2019)
Economy globalization has changed the course of the history all around the world. The local way of thinking is being substituted by an international one, where economies look for avoiding the protectionist politics that they had in the past, to let the free exchange go on. For that reason, it is necessary to focus big efforts in order to prepare students of International Business programs, to contribute to the international trade growth in different regions of the country, create programs for internationalization and be the support for the insertion in the different markets around the world. This text is a study of International Business, starting by the conceptualization that takes into account the historical basis, its interpretation and the terminological differences, which will let the reader approach the comprehension of the discipline in order to analyze the different theories that have made part of the development of international trade through scientific studies about the topic. On the other hand, it is necessary to consider the advances of the international business at a regional, a national and a global level, which makes it easy to understand the different sceneries where the trade has been developed.